البناء العاملي لمقياس القلق الاحصائي دراسة على عينة من طلبة الدراسات العليا في كلية التربية بجامعة تشرين - بوبو منذر (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
هدف هذا البحث إلى تحليل البنية العاملية لمقياس القلق الإحصائي باستخدام التحليل العاملي. قام الباحث بتطبيق النسخة العربية من المقياس الذي قام بتعريبه (أبو هاشم،2002) على عينة من طلبة الدراسات العليا في كلية التربية بجامعة تشرين، ومن ثم قام الباحث باستخراج الخصائص السيكومترية للمقياس في بحث سابق، وقد تبين تمتع المقياس بدلالات صدق وثبات عالية. ومن أجل التأكد من صدق بنية المقياس قام الباحث بهذا البحث. وقد توصل البحث الحالي إلى مجموعة من النتائج تشير إلى تشبع الجزء الأول من المقياس بثلاثة عوامل فسرت 63.26% من التباين، كما تبين تشبع القسم الثاني من المقياس بثلاثة عوامل فسرت 69.41% من التباين. كما تبين أن المقياس ككل يتشبع على مكونين يفسر الأول (39.86%) من التباين الكلي، ويفسر المكون الثاني (36.45%) من التباين الكلي. وقد توافقت البنية الهيكلية التي تم استخرجها مع حقيقة فقرات المقياس النظرية مما يعزز الثقة بقدرة المقياس على قياس القلق الإحصائي لدى طلبة الدراسات العليا. This study aimed to extract the psychometric characteristics of the Statistical Anxiety Scale when applied to a sample of graduate students the Faculty of Education, Tishreen University, to ensure the ability to using the statistical anxiety scale to diagnose postgraduate students’ statistical anxiety reliability. Statistical anxiety scale (which was translated by into Arabic Abou Hashem, 2002) has been applied on a sample of research postgraduate students in the courses phase and in the dissertation phase in the Faculty of Education at the Tishreen University. The study results indicate a high significant internal consistency and statistically significant of the scale items, the scale also enjoyed a high degree of reliability. The items that to cause concern were extracted from the sample, and were arranged according to the level of concern caused by calculating the specific weight of each item. It was verified of a set of hypotheses that confirmed the scale validity and reliability.